Islamic Educational Values in Cultural Harmonization in Places of Worship - Raihanah Raihanah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Understanding of religion is often not in line with the culture that has taken root in society. This often triggers conflicts in an area. Understanding ethnicity and religious understanding also often triggers ethnic conflicts that lead to criminal behavior such as the tragedy of the dispute between ethnic Dayaks and ethnic Madurese in Central Kalimantan in 2001. The purpose of this study is to find forms of cultural and religious interaction at the Pusaka Mosque in the District of Banua Legacy during the religious and cultural Dayak Ma'anyan people who settled in the district of Banua Lawas until the entry of Islam in the Tabalong district and found a form of harmonization symbolized at the Heritage Mosque and religious activities carried out by local residents and pilgrims who came. This research uses a qualitative method with James P. Spradley' s ethnography research type and data collection by observation is not involved as well as in-depth interviews of findings from interviews that have the potential to be explored further. The results showed that the Pusaka Mosque in Banua Lawas sub-district was a very beautiful reflection of tolerance as indicated by the construction of the mosque above the pesantren (place of worship) of the Dayak Ma'anyan people who first settled in the area. Its construction was inseparable from the participation of the Dayak Maanyan tribes who had just converted to Islam and who still guarded the religion of their Kaharingan ancestors. This research contributes to the issues of religious harmonization and moderation that are being put forward by the government to bring about tolerance, efforts to deradicalize and overcome the disintegration of the nation.